2019
DOI: 10.1007/s41999-019-00251-8
|View full text |Cite
|
Sign up to set email alerts
|

How does decisional capacity evolve with normal cognitive aging: systematic review of the literature

Abstract: Key summary pointsAim The complexity of decision-making involves many neurological functions and structures which are potentially altered by cognitive aging. Findings Our systematic review shows a decrease in processing speed in normal aging, usually compensated by experience. Nevertheless, in the case of decisions that cannot be based on previous experience, decision-making will be more difficult for older adults. Compared to younger adults, older ones will be more inclined to maintain existing achievements t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
13
2
2

Year Published

2021
2021
2025
2025

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(17 citation statements)
references
References 62 publications
(90 reference statements)
0
13
2
2
Order By: Relevance
“…Thus, when older adults are given enough time or when they can rely on past experiences, decision-making function remains preserved pp. 351-370 in [1,23]. Furthermore, the decision-making processes involved in these tests include executive functions, but also motivation and reward processes.…”
Section: Introductionmentioning
confidence: 99%
“…Thus, when older adults are given enough time or when they can rely on past experiences, decision-making function remains preserved pp. 351-370 in [1,23]. Furthermore, the decision-making processes involved in these tests include executive functions, but also motivation and reward processes.…”
Section: Introductionmentioning
confidence: 99%
“…When the stimulation is no longer new, the posterior-anterior shift is reduced, and this could possibly indicate that learning and the lifetime experience in decision-making and problem solving can compensate for the age-related decrease in processing speed. This should be taken into consideration especially in scenarios where new information is being discussed, by repeating information, clarifying terminology and providing sufficient time for the patient to make an autonomous decision ( 39 ). Supported decision-making is an emerging paradigm in which people get help from others to understand and address choices they encounter in everyday life.…”
Section: Discussionmentioning
confidence: 99%
“…Encouragement and shared decision making are also considered essential. Training in and implementation of these measures to enhance autonomous DMC can ultimately reduce the stigma associated with SMI in older populations ( 39 , 46 ).…”
Section: Discussionmentioning
confidence: 99%
“…The executive functions are also affected due to the changes in the dorsolateral prefrontal cortex in cognitive ageing, especially the decrease in the reactivity of processing speed and working memory [40]. It is suggested that the cognitive changes that occur due to normal ageing are mostly in executive functions.…”
Section: Discussionmentioning
confidence: 99%
“…Like other cognitive abilities, decision making is affected by an age-related slowdown in information processing speed. However, cognitive capacity can be maintained and adequately expressed if the person is provided with sufficient time and clear explanations [40]. While the structural changes due to ageing are most prominent in the prefrontal cortex, medial temporal lobes are affected in 10-20% of normal individuals.…”
Section: Discussionmentioning
confidence: 99%